SYSTEM FOR ASSESSING THE CYBERSECURITY STATE BASED ON CYBERDIPLOMACY INDICATORS - Kazmirchuk, Svitlana; Shulha, Volodymyr (Science-based technologies, 2026)
The article addresses the problem of formalized assessment of a state’s cybersecurity level under conditions of growing hybrid threats, uncertainty of initial data, and the need to account not only for technical, but also legal, organizational, and foreign-policy aspects. It is shown that existing international index systems, maturity models, and regulatory approaches (GCI, NCSI, CMM, NIS2, NIST, OECD) do not provide for the construction of an integrated adaptive assessment system suitable for use at the state level in conditions of military confrontation and dynamic transformation of cyber threats. The purpose of the study is to develop and implement in software a system for assessing the level of a state’s cybersecurity, based on a formalized system of criteria, including a cyberdiplomacy dimension, and implementing a multicriteria fuzzy method for integrating expert assessments. The proposed system makes it possible to account for linguistic expert evaluations, different weights of criteria and sub-criteria, and to operate under conditions of incomplete and fuzzy information. The paper develops a structural model of the assessment system consisting of a data input and management subsystem and an assessment and data processing subsystem, as well as the corresponding functional modules for authentication, initialization of criteria and sub-criteria, formation of scales and reference benchmarks, determination of weighting coefficients, expert assessment, fuzzification, aggregation, defuzzification of results, and report generation. A basic algorithm for the system’s operation is proposed, ensuring consistent processing of expert data and the formation of an integral indicator of the cybersecurity level. To verify the correctness and sensitivity of the method, experimental modeling of the system’s operation was conducted for three scenarios corresponding to low, medium, and high levels of the cybersecurity state. The experimental results confirmed the monotonic behavior of the integral indicator when transitioning between scenarios and the unambiguous classification of levels based on the generalized Hamming distance to reference benchmarks. A prototype software application of the state cybersecurity assessment system was developed, providing automation of the collection of expert assessments, their processing, and visualization of results in the form of an integral level and criterion-based evaluations. The proposed approach can be used as a decision-support tool in the field of state cyber policy, strategic planning, and international cyberdiplomatic cooperation.